2016
DOI: 10.1097/yct.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Practice in Spain

Abstract: The ECT practice has significantly improved in Spain in recent years. Overall, Spanish facilities seem to comply with established clinical guidelines; however, specific concerns were identified, meaning there is still further scope for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 0 publications
2
21
3
1
Order By: Relevance
“…Following our ECT unit protocol and national and international standards, 29, 30, 31 all the patients were treated with bifrontotemporal, brief pulse (0.5–1 ms) ECT, using a Thymatron System IV device (Somatics, Lake Bluff, IL, USA). Anesthesia was induced with intravenous thiopental (2–2.5 mg kg −1 ) and succinylcholine (0.5 mg kg −1 ) was used for muscle paralysis.…”
Section: Methodsmentioning
confidence: 99%
“…Following our ECT unit protocol and national and international standards, 29, 30, 31 all the patients were treated with bifrontotemporal, brief pulse (0.5–1 ms) ECT, using a Thymatron System IV device (Somatics, Lake Bluff, IL, USA). Anesthesia was induced with intravenous thiopental (2–2.5 mg kg −1 ) and succinylcholine (0.5 mg kg −1 ) was used for muscle paralysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, heterogeneity in ECT delivery, both nationally and internationally, is a concern. A comprehensive contemporary review of worldwide ECT practice and variability demonstrated substantial heterogeneity [2] with high variability in the United States [3][4][5], Canada [6,7], Australia [8], the Netherlands [9], Belgium [10], Central and Eastern Europe [11], Greece [12], Spain [13], the Baltic States [14], Saudi Arabia [15], South Africa [16], Nigeria [17], Russia [18], Thailand [19], Japan, [20], India [21] and other Asian countries [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This international perspective has been essential in discussing best practices in the clinical administration of ECT based on evidence from researchers and practitioners around the world. For example, in 2006, the same year that articles were published on ECT practice in Australia, 1 Belgium, 2 and Spain, 3 a series of articles in the journal critiqued the clinical guidelines on the practice of ECT in England and Wales by the National Institute for Clinical Excellence (NICE). 48 …”
mentioning
confidence: 99%